Preparation and characterisation of atorvastatin and curcumin‐loaded chitosan nanoformulations for oral delivery in atherosclerosis. Issue 1 (13th January 2017) - J.B., Varuna Kumara; Ramakrishna, Sistla; Madhusudhan, Basavaraj
Abstract : Atorvastatin known to be a potential inhibitor of HMG‐CoA reductase involved in the synthesis of cholesterol. It is touted as miracle drug due to its profound effect in decreasing the low‐density lipoproteins in blood. Unfortunately, the high dosage used poses side‐effects relatively in comparison to other statins. On the other hand, curcumin has a diverse therapeutic potential in health and disease. However, the poor aqueous solubility and low bioavailability hinders the therapeutic potential of it when administrated orally. Therefore, it was thought to minimise the frequency of atorvastatin doses to avoid the possibility of drug resistance and also to overcome the limitations of curcumin for desirable therapeutic effects by using nanocarriers in drug delivery. In this investigation, synergistic effect of atorvastatin and curcumin nanocarriers was encapsulated by chitosan polymer. The chitosan nanocarriers prepared by ionic gelation method were characterised for their particle size, zeta potential, and other parameters. The drug‐loaded nanocarriers exhibited good encapsulation efficiency (74.25%) and showed a slow and sustained release of atorvastatin and curcumin 60.36 and 61.44%, respectively, in a span of 48 h. The drug‐loaded nanocarriers found to be haemocompatible and qualified for drug delivery in atherosclerosis.